Combination of shear-wave elastography with ultrasonography for detection of breast cancer and reduction of unnecessary biopsies: a systematic review and meta-analysis - Park, Sun-young; Kang, Bong Joo (Ultrasonography (Seoul, Korea), 2021)
This study was undertaken to compare the diagnostic performance and biopsy reduction rate of combined shear-wave elastography (SWE) and B-mode ultrasonography (US) versus B-mode US alone for breast lesions and to determine the most discriminatory parameter in SWE. A systematic review and meta-analysis were conducted. The resources for the study were obtained from MEDLINE, Embase, Cochrane Library, and KoreaMed on August 17, 2018. The quality of the articles was evaluated using the Scottish Intercollegiate Guidelines Network (SIGN) tool. Twenty-five articles with 5,147 breast lesions were selected. The meta-analysis showed pooled sensitivities of 0.94 and 0.97 (P=0.083), pooled specificities of 0.85 and 0.61 (P=0.009), and area under the receiver operating characteristic curve (AUC) of 0.96 and 0.96 (P=0.095) for combined SWE and B-mode US versus B-mode US alone. When SWE was combined with B-mode US, the Breast Imaging Reporting and Data System category changed from 4 to 3 in 71.3% of the tests, decreasing the frequency of unnecessary biopsies by 41.1%. All four parameters of SWE (the color grade of lesion stiffness, maximum elasticity, mean elasticity, and color grade of lesion stiffness/homogeneity of the lesion) improved the specificity when they were added to B-mode US. The AUC for each SWE parameter was 0.99, 0.96, 0.96, and 0.93, respectively. Adding SWE to B-mode US not only provides additional diagnostic information for differentiating between benign and malignant breast lesions, but also decreases the likelihood of unnecessary biopsies.